2022
DOI: 10.1177/00812463221093525
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative care for mental health in South Africa: a qualitative systematic review

Abstract: Collaborative care for mental health is a strategy that restructures the roles of health care providers, and sectors outside of health care provision, to encourage a team-based approach in dealing with mental illness. Previous research proposed a collaborative care strategy to make mental health care more accessible and culturally appropriate. This study systematically reviewed the available literature to produce a summary of collaborative care in the context of mental health care in South Africa. More specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…A 2021 scoping review of the role of public private partnerships in the provision of primary care services found that PPPs have the potential to increase access and to facilitate the provision of prevention and treatment services for certain target groups [ 29 ]. Moreover, collaborative efforts between governments, non-profit organizations, and international partners have also proven to be effective in addressing mental health service gaps through community-based interventions, training programs for health workers, and the integration of mental health into primary healthcare services in countries like Uganda [ 30 ], South Africa [ 31 ] and Kenya [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…A 2021 scoping review of the role of public private partnerships in the provision of primary care services found that PPPs have the potential to increase access and to facilitate the provision of prevention and treatment services for certain target groups [ 29 ]. Moreover, collaborative efforts between governments, non-profit organizations, and international partners have also proven to be effective in addressing mental health service gaps through community-based interventions, training programs for health workers, and the integration of mental health into primary healthcare services in countries like Uganda [ 30 ], South Africa [ 31 ] and Kenya [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…The evolution of mental health care models in Africa has been characterized by a shift towards more collaborative and integrated approaches. Truter (2023) provides a comprehensive review of collaborative care for mental health in South Africa, emphasizing the restructuring of roles among healthcare providers and sectors outside of healthcare provision. This strategy aims to make mental health care more accessible and culturally appropriate.…”
Section: Evolution Of Mental Health Care Modelsmentioning
confidence: 99%
“…Community-based approaches in African contexts have increasingly focused on integrating mental health care into existing social and cultural frameworks. Truter's (2023) review of collaborative care in South Africa underscores the importance of community engagement in mental health care. The study highlights the need for improved infrastructure, formalized roles and relationships, enhanced communication, and better training and education to support collaborative care models.…”
Section: Ommunity-based Approaches In African Contextsmentioning
confidence: 99%
See 1 more Smart Citation
“…service gaps through community-based interventions, training programs for health workers, and the integration of mental health into primary healthcare services in countries like Uganda [30], South Africa [31] and Kenya [32].…”
Section: Plos Onementioning
confidence: 99%